Synthesis of Substituted Phenyl 4 thiazolidin 3 yl 1 3 4 thiadiazol 5 yl Coumarin Derivatives and their Antifungal Activities - Verma, Sonia (International Journal of Pharmaceutical & Biological Archive, 2014)
Synthesis of Substituted Phenyl 4 thiazolidin 3 yl 1 3 4 thiadiazol 5 yl Coumarin Derivatives and their Antifungal Activities